TOXIC POSITIVITY DALAM KONTEN MOTIVASI ISLAMI: BAHAYA DI BALIK KATA-KATA PENYEMANGAT - Nisbaul Nabawi (NIHAYAH: Journal of Islamic Studies, 2025)
The surge of Islamic motivational content on social media has generated a form of religious communication that adopts the language of instant positivity typical of pop psychology. Behind phrases like “Don’t be sad, Allah is with you” or “Stay strong, Allah will make a way,” lies a practice of toxic positivity—urging constant happiness and gratitude without validating negative emotions. This study critically examines how toxic positivity manifests in popular Islamic content and its psychological impact on young Muslims. Employing critical discourse analysis on 300 #MotivasiIslami posts from Instagram and TikTok, alongside digital ethnography and interviews with 20 content consumers aged 18–30, the study identifies three dominant patterns: denial of negative emotions, simplistic religious solutions, and misuse of the concept of tawakkul. Findings reveal that 28% of respondents felt guilty for not being able to maintain constant positivity. The research highlights how Qur'anic verses or prophetic traditions are selectively used to support shallow affirmations, and how the attention economy commodifies spirituality. The study underlines the need for religious media literacy that promotes a balanced integration of psychology and spirituality, and a more holistic narrative of sabr (patience). It recommends developing content that not only encourages but also embraces emotional complexity within the framework of faith.